Aplikasi model hidrologi ketersediaan air untuk perbaikan sistem operasi irigasi :: Studi kasus pada DAS Pekatan Lombok Barat - ABDULLAH, Sirajuddin Haji ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Calculation of water availability for irrigation can be held by using a flow rain model. This research wants to apply an hydrology model to calculate water availability of irrigation and needs in a development. Taking is in a real time condition in an attempt to support a rehabilitation of irrigation operation system and to make possible widely developing of farming area, by taking a research location of Watershed of Pekatan of West Lombok. The calculation of water availability in the river is using an approach with Mock and Tank methods. Test for Model appropriateness is caused to be effective by involving coefficient of correlation, relative error, volume error and- T-Test. Even by raising data of ?h month of rainfall and ?hmonth of E use Thomas-Fiering’s to model of product, resulted data are used a s a model application to calculate available discharge in the d am, while the calculation of needs discharge follows the guideline of irrigation water management as an implementation standard of irrigation operation system for several years coming.